Erratum: Influence of annealing on the properties of (Cd, Mn)Te crystals. Issue 4 (17th April 2015) - Witkowska‐Baran, M.; Kochanowska, D. M.; Mycielski, A.; Jakieła, R.; Wittlin, A.; Knoff, W.; Suchocki, A.; Nowa‐kowski, P.; Korona, K.
Abstract: The authors have completed their institutions to properly reflect the contributions of the affiliated institutions.